Sobre la redención y la burla: análisis de la carta 256 de Focio de Constantinopla. - Rivera Díaz, Pedro (Scripta Mediaevalia, 2025)
The letters of Photios of Constantinople (c. 810/820-after 893) represent a substantial body of information concerning the life of one of Byzantium's most prominent political and intellectual figures. Notably, in addition to the distinguished recipients and correspondents, including some family members, there are abundant demonstrations of his extensive knowledge across various fields such as mythology, politics, and theology. Despite this, scholarly attention to the letters, in general and in particular, has been scant. Consequently, the objective of this study is to analyze the Ep. 256, addressed to his brother Tarasios, in which Photios conducts a meticulous examination of the sense of three terms: περίψημα and κάθαρμα (1 Cor. 4:13), and ἐκολάφισαν (Mt. 26:67). This analysis will explore the methodology used to elucidate the meaning attributed to each term, as well as the sources employed to support his arguments. The aim is to enhance the understanding of Photios' lexical analysis and the relationship between his letters and other writings, including those by the patriarch as well as those by other authors.